Faktor-faktor yang Mempengaruhi Kinerja Pegawai di Dinas Perdagangan Koperasi dan Usaha Kecil Menengah Kabupaten Cilacap - Arum Suryaningtyas; Sri Sundari; Herwiek Diyah Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this research is to analyze the partial significance of the influence of work motivation, work discipline, organizational commitment, and competence on employee performance in DPKUKM Cilacap Regency. The sample in this study includes the entire population, consisting of 38 employees. The sampling technique used is proportional random sampling. Data analysis is conducted using multiple linear regression. The results of this research is work motivation, organizational commitment, and competence have a significant positive effect on the performance of DPKUKM employees in Cilacap Regency. However, work discipline does not have a significant effect on the performance of DPKUKM employees in Cilacap Regency. The implications of this research suggest that DPKUKM Cilacap Regency needs to enhance employee performance by: 1) increasing work motivation by improving employee compliance with applicable regulations; 2) enhancing organizational commitment by strengthening the sense of family among employees; 3) improving competence by training employees in precision at work. Although work discipline does not significantly influence employee performance, DPKUKM Cilacap can improve punctuality in working hours through stricter monitoring of office entry, break, and departure times.